2016
DOI: 10.5539/gjhs.v8n10p34
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lifestyle Educational Program in Health Promoting Behaviors and Menopausal Symptoms in 45-60-Year-Old Women in Marvdasht, Iran

Abstract: Lifestyle education was effective in health promoting behaviors and menopausal symptoms. After the educational intervention, health promoting behaviors increased and menopausal symptoms decreased in the postmenopausal women. Therefore, educational interventions based on health promoting lifestyles can be used as an appropriate strategy to reduce postmenopausal women's menopausal symptoms and improve their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
4
21
0
1
Order By: Relevance
“…Our observations are consistent with many studies which reported the effectiveness of health education interventions focused on health-promoting lifestyle modifications. e findings of education interventions based on lifestyle modifications were effective in improving menopausal symptoms, and HPB [28][29][30][31] of PMW is consistent with that of the current study. A Chinese study also showed that a 12-week intervention helped the PMW to change HPB positively [32].…”
Section: Discussionsupporting
confidence: 90%
“…Our observations are consistent with many studies which reported the effectiveness of health education interventions focused on health-promoting lifestyle modifications. e findings of education interventions based on lifestyle modifications were effective in improving menopausal symptoms, and HPB [28][29][30][31] of PMW is consistent with that of the current study. A Chinese study also showed that a 12-week intervention helped the PMW to change HPB positively [32].…”
Section: Discussionsupporting
confidence: 90%
“…While deaths depending on direct violence affect the male population, the indirect deaths kill children, women and elders more. In Iraq between 1990-1994, infant deaths had shown this reality in its more bare form with an increase of 600% (4). The war taking five years increases the child deaths under age of 5 by 13%.…”
Section: Mortalities and Morbiditiesmentioning
confidence: 99%
“…[17] As the most cost-effective way to avoid, as well as alleviate, many of the health problems is by taking preventive measures such as diet, exercise, and medical examination, and in this study, women were educated on these issues. A similar study by Nazari et al [18] showed that the educational interventions based on health promoting lifestyles can be used as an appropriate strategy to reduce postmenopausal women's menopausal symptoms and improve their health.…”
Section: Discussionmentioning
confidence: 99%